2009
DOI: 10.1080/17470910802424445
|View full text |Cite
|
Sign up to set email alerts
|

The effect of deception on motor cortex excitability

Abstract: Although a number of recent neuroimaging studies have examined the relationship between the brain and deception, the neurological correlates of deception are still not well understood. The present study sought to assess differences in cortical excitability during the act of deception by measuring motor evoked potentials (MEPs) during transcranial magnetic stimulation (TMS). Sports fanatics and low-affiliation sports fans were presented with preferred and rival team images and were asked to deceptively or hones… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
10
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 19 publications
4
10
0
Order By: Relevance
“…When they thought the left hand part of the music was being played by another person, the MEPs in the left arm were greater, and MEPs increased as the participant's empathy increased [75]. Further, previous work by our lab demonstrated that adopting another's perspective (e.g., pretending to be a fan of an opposing sports team) led to greater left motor cortex/right hand MEPs [76].…”
Section: Motor Evoked Potentials (Meps)mentioning
confidence: 61%
“…When they thought the left hand part of the music was being played by another person, the MEPs in the left arm were greater, and MEPs increased as the participant's empathy increased [75]. Further, previous work by our lab demonstrated that adopting another's perspective (e.g., pretending to be a fan of an opposing sports team) led to greater left motor cortex/right hand MEPs [76].…”
Section: Motor Evoked Potentials (Meps)mentioning
confidence: 61%
“…Two additional studies used single-pulse TMS to probe motor cortex excitability during deception (Duzel et al, 2003;Kelly et al, 2009). …”
Section: Tms Findingsmentioning
confidence: 99%
“…Finally, two studies employed single-pulse TMS to probe the excitability of primary motor cortex during deceptive behaviour (Kelly et al, 2009;Lo, Fook-Chong, & Tan, 2003) since a number of neuroimaging studies have reported stronger motor cortex activation (especially in the left hemisphere) to deceptive than honest responses (Ganis, Kosslyn, Stose, Thompson, & Yurgelun-Todd, 2003;Kozel et al, 2005;Langleben et al, 2002;Spence et al, 2001Spence et al, , 2004. In the first study (Lo et al, 2003), MEPs were recorded from the participants' left or right thumb in response to single TMS pulses delivered to the contralateral primary motor cortex (in different blocks).…”
Section: Tms Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…When they thought the left hand part of the music was being played by another person, the MEPs in the left arm were greater, and MEPs increased as the participant's empathy increased (Novembre, Ticini, Sch眉tz-Bosbach, & Keller, 2012). Further, previous work by our lab demonstrated that adopting another's perspective (e.g., pretending to be a fan of an opposing sports team) led to greater left motor cortex/right hand MEPs (Kelly et al, 2009). Centered on first-person perspective, a number of researchers employed TMS induced motor-evoked potentials (MEPs) to measure lateralized cortical excitability during the presentation of self-descriptive adjectives (Molnar-Szakacs, .…”
mentioning
confidence: 99%